1998
DOI: 10.1038/sj.bjp.0702177
|View full text |Cite
|
Sign up to set email alerts
|

Impaired function of alpha‐2 adrenoceptors in smooth muscle of mesenteric arteries from spontaneously hypertensive rats

Abstract: 1 The a 2 -adrenoceptor function in mesenteric arteries of spontaneously hypertensive rats (SHR) was investigated by comparing membrane potential changes in response to adrenergic agonists in preparations from female SHR, Wistar-Kyoto (WKY) and normotensive Wistar rats (NWR). 2 Resting membrane potential was found to be less negative in mesenteric arteries from SHR than in those from NWR and WKY. Apamin induced a decrease in the membrane potential of mesenteric artery rings without endothelium from NWR and WKY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…This could be attributed to impaired activity of K ϩ channels, as was observed for the responses to ␣ 2 -adrenergic agonists, 23 rather than to impaired synthesis, release, or diffusion of EDHF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This could be attributed to impaired activity of K ϩ channels, as was observed for the responses to ␣ 2 -adrenergic agonists, 23 rather than to impaired synthesis, release, or diffusion of EDHF.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies already reported an interaction between NO and EDHF systems, 23,32 it is likely that the reduced hyperpolarization induced by ACh in untreated SHR mesenteric arteries, due to the impairment of K ϩ channels, may upregulate the production of NO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous articles, 13,14 we reported that SHR mesenteric artery smooth muscles are less polarized than those of normotensive Wistar rats (NWR). This was attributed to different alterations, such as impairment of the activity of K ϩ channels coupled to ␣ 2 -adrenoceptors or diminished NO production in the SHR.…”
mentioning
confidence: 99%